2021
DOI: 10.18632/aging.202746
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MNX1-AS1 drives aggressive laryngeal squamous cell carcinoma progression and serves as a ceRNA to target FoxM1 by sponging microRNA-370

Abstract: Long non-coding RNA (LncRNA) MNX1 antisense RNA 1(MNX1-AS1) is associated with the pathology of numerous cancers. But, the role and underlying pathways of MNX1-AS1 in the regulation of laryngeal squamous cell carcinoma (LSCC) is not known. We demonstrated remarkably elevated levels of MNX1-AS1 in the LSCC tissues, which was correlated with poor disease prognosis. Moreover, MNX1-AS1-silencing strongly suppressed LSCC cell proliferation, migration, and invasion. We also demonstrated that MNX1-AS1 sequesters that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…LncRNA could act as a competing endogenous RNA (ceRNA) by competitively binding targeted miRNAs, which further participated in the regulation of carcinogenesis of human tumors, including LSCC. For example, MNX1-AS1 promoted LSCC progression and served as a ceRNA to target FoxM1 by sponging miR-370 [ 27 ]. TRPM2-AS facilitated cell metastasis by decreasing miR-138 and increasing SOX4 expression in LSCC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA could act as a competing endogenous RNA (ceRNA) by competitively binding targeted miRNAs, which further participated in the regulation of carcinogenesis of human tumors, including LSCC. For example, MNX1-AS1 promoted LSCC progression and served as a ceRNA to target FoxM1 by sponging miR-370 [ 27 ]. TRPM2-AS facilitated cell metastasis by decreasing miR-138 and increasing SOX4 expression in LSCC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have reported that lncRNAs serve as ceRNAs to sponge miRNAs [ 29 31 ]. The RegRNA 2.0 software was used to predict target miRNAs of lncRNA ENSMUST_147219.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al revealed that HOTAIR can bind with miR-206, facilitating STC2 and activating the PI3K/AKT signal pathway, thereby regulating cell biological functions in HNSCC [ 37 ]. Cui et al disclosed that MNX1-AS1 competitively bounds miR-370, regulating FoxM1 and thereby modulating laryngeal squamous cell carcinoma progression [ 38 ]. These findings might provide a valuable perspective for future research.…”
Section: Discussionmentioning
confidence: 99%